TRAINING PEMBAGIAN WARIS DALAM AL-QUR’AN PERSPEKTIF NASAR HAMID ABU ZAID DI HIMPUNAN MAHASISWA YAYASAN AL-KAHFI - Muhammad Hariyadi; Devy Meris Rowanti; Kerwanto Kerwanto; Mulyani Mulyani; Ikhlas Budiman; Ikhwan Ansori (MPP: Lembaga Penelitian Dan Studi Kebijakan, 2024)
This papper is an attempt to integrate the method of interpreting the Al-Qur'an developed by Nasr Hâmid Abû Zaid, namely the theory of takwil al-Qur'an. This study found that the takwil theory that constructed by Nasr Hâmid Abû Zaid emphasizes the importance of paying attention to the role of the author of the text, interpreter and context, as a theory for interpreting the Qur'an. Once applied, this theory can provide an interpretation that can reveal the side of justice in the concept of distribution of inheritance in the study of Islamic law. The approach used in this study is a hermeneutic approach in order to understand the interpretation of religious texts which are considered relevant to the concept of distribution of inheritance in the study of Islam law